Interconnection of historical and artistic truth in the Cossack song folklore of the Dnieper region (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
This article for the first time describes artistic and Cossack folklore of center and lower parts of the Dnipro banks of the as integral genre-thematic system is in the plan of methodology of study of dominant signs of its poetics, aesthetics, conception of hero, structure of text. It is defined that it is a degree of authenticity of zobrazhennikh events of the Cossacks in Ukrainian folklore, in what measure Cossack folklore is a historical source.
Keywords: cossack folklore; the cossacks; genre